Implementing policy innovations - Resource dependence, struggle for discursive hegemony and institutional inertia in the Dutch river policy domain - Margo Van den Brink; Sander Meijerink (European Regional Science Association (ERSA), 2005)
Due to climate changes, the volume of the water flowing in the rivers will continue to increase and the sea level will continue to rise. To be able to cope with potential future flood disasters, Dutch policy makers now try to elaborate and implement a new safety concept, called 'space for the river'. The basic idea of this new safety concept is to increase the amount of space for the rivers, and by that to enlarge their discharge capacity. The aim of the large national 'Space for Rivers' project is to develop river-widening measures which improve both the safety of the inhabitants and the spatial quality of the riverine areas at the same time. Replacing dikes, digging out old river branches or creating new ones (bypasses) are some examples of possible measures. This paper focuses on the institutional dynamics brought about by this new safety concept. The national water management agency Rijkswaterstaat realised that for the implementation of this new safety concept it is largely dependent on the cooperation of other national ministries, provinces, municipalities, water boards, NGOs and inhabitants of the areas along the main rivers. Therefore, an innovative policy process was designed aimed at joint learning, and at creating administrative and societal support for an ambitious river policy program. During this process three key-dilemmas became apparent. First, there is a permanent tension, partly caused by financial scarcity, between the objectives of safety and spatial quality. Secondly, in spite of the interactive policy design chosen, existing institutions, such as the procedure for large scale infrastructure projects ('PKB-procedure'), do support governmental hierarchy rather than horizontal modes of governance. Finally, there is a tension between long term and short term policy objectives. In other words: what relative importance is attached to either reaching safety standards in the short run or anticipating future river discharges? The main argument of this paper is that to better understand these dilemmas we need to reconstruct the frames of reference of the parties involved and the different rules of the game water managers and spatial planners are used to play.
Keywords: 330